1988
DOI: 10.1016/0014-5793(88)80432-0
|View full text |Cite
|
Sign up to set email alerts
|

Thiol reagents are substrates for the ADP‐ribosyltransferase activity of pertussis toxin

Abstract: Thiols such as cysteine and dithiothreitol are substrates for the ADP-ribosyltransferase activity of pertussis toxin. When cysteine was incubated with NAD ÷ and toxin at pH 7.5, a product containing ADP-ribose and cysteine (presumably ADP-ribosylcysteine) was isolated by high:performance liquid chromatography, and characterized by its composition and release of AMP with phosphodiesterase. Cysteine has a Km of 105 mM at saturating NAD + concentration. The ability of thiols to act as a substrate is one explanati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
9
1

Year Published

1992
1992
1997
1997

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 9 publications
1
9
1
Order By: Relevance
“…This suggests that, although similar strategies were followed to purify these enzymes, different products were obtained. The affinity of the purified enzyme for cysteine was much higher than that exhibited by pertussis toxin (Km = 100 mM) [16], but similar to that shown by the human enzyme (Km = 4.4 mM) [21].…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…This suggests that, although similar strategies were followed to purify these enzymes, different products were obtained. The affinity of the purified enzyme for cysteine was much higher than that exhibited by pertussis toxin (Km = 100 mM) [16], but similar to that shown by the human enzyme (Km = 4.4 mM) [21].…”
Section: Discussionsupporting
confidence: 60%
“…For cholera toxin [15] and pertussis toxin [16], it has been demonstrated that, in the absence of the protein target, the free amino acid may act as an acceptor for ADP-ribose. On the basis that endogenous enzymes may share the same enzyme mechanism as the bacterial toxins, this property was used to identify endogenous ADP-ribosyltransferases.…”
Section: Introductionmentioning
confidence: 99%
“…However, the effect of pertussis toxin may not be related to modification of a regulatory protein in the traditional manner. It has been shown that the site of ADP ribosylation of G proteins by pertussis toxin is a conserved cysteine residue located four amino acids from the COOH terminus of the (J.-subunit of the proteins [153], and thiol compounds may also function as ADP ribosylation substrates for pertussis toxin in vitro [156). The effect of pertussis toxin on relaxation and cGMP production might be due to inactivation of critical thiol groups necessary for the activation of soluble guanylate cyclase.…”
Section: Glyceryl Trinitrate-biphasic Relaxation Patternmentioning
confidence: 99%
“…substrate (Lobban & van Heyningen, 1988). Proteolytic degradation at the carboxyl terminus, believed to result in the removal of the two terminal amino acids, appeared to inhibit ADP-ribosylation but not to affect association of a with fiy (Neer et al, 1988).…”
mentioning
confidence: 92%